2014
DOI: 10.1115/1.4028350
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Verified Study of Regeneration-Induced Forced Response in Axial Turbines

Abstract: Geometrical variations occur in highly loaded turbine blades due to operation and regeneration. To determine the influence of such regeneration-induced variances of turbine blades on the aerodynamic excitation, a typical stagger angle variation of overhauled turbine blades is applied to stator vanes of an air turbine. This varied turbine stage is numerically and experimentally investigated. For the aerodynamic investigation of the vane wake, computational fluid dynamics (CFD) simulations are conducted. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…All these studies have shown that the influence of several kinds of geometric variation in an upstream stator vane row is significant. These results were verified by experimental investigations in [7,9]. The aerodynamic excitation mechanisms occuring in a high pressure turbine stage were numerically investigated in [10].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…All these studies have shown that the influence of several kinds of geometric variation in an upstream stator vane row is significant. These results were verified by experimental investigations in [7,9]. The aerodynamic excitation mechanisms occuring in a high pressure turbine stage were numerically investigated in [10].…”
Section: Introductionsupporting
confidence: 53%
“…The analyzed blade row is not adjacent to the varied vane row. The vibration amplitude is numerically predicted using a unidirectional fluid-structure approach validated experimentally in [9]. The results are compared with the reference case, and additionally with a variation in the vane row adjacent to the excited blade.…”
Section: Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the lower sensitivity on the vibration amplitude in Mode 3 than Mode 2, even the unsteady pressure fluctuation is suppressed more for Mode 3 than for Mode 2 with the 3D blading of the IGV. Previous studies concern parametric variations in adjacent blade rows [23,28]. This study shows that forced response of a target row can be considerably affected by varying aerodynamic design of blades remote from it.…”
Section: Aeroelastic Resultsmentioning
confidence: 84%
“…In addition to those efforts to develop fast and accurate tools to predict forced response, many studies have been conducted to validate the prediction tools. Aschenbruck and Seume [23] presented the experimental verification of regeneration-induced forced response in a turbine. Bittner et al [24] showed experimental validation of the forced response analysis using a time-linearized method in a high speed compressor.…”
Section: Forced Response Analysismentioning
confidence: 99%